Bioaccessibility of apigenin from Mangifera indica (Water Lily var.) during in vitro gastrointestinal digestion - Zulkifli, Marina; Ismail, Amin; Loh, Su Peng; Jailani, Fadhilah; Kassim, Nur Kartinee (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
The bioaccessibility property of apigenin from Mangifera indica (Water Lily var.) was investigated using in vitro gastrointestinal digestion model. Two digestion stages were simulated namely the gastric and small intestinal digestion by using different enzymes and physiological conditions that mimicked the digestion process. Following digestion, the bioaccessible apigenin was analysed using HPLD-DAD-MS. Results showed that the apigenin fraction in intestinal phase was higher than in gastric phase with amounts 1.03 ± 0.35 mg/100 g DW and 0.50 ± 0.08 mg/100 g DW, respectively. After 1 h exposure to gastric juice, the bioaccessibility of apigenin was 20.26 ± 3.06% with 79.74 ± 3.06% losses during the digestion, whereas in intestinal phase, the percentage of bioaccessibility significantly increased to 41.53 ± 13.99% and 58.47 ± 13.99% losses after 2 h treatment with pancreatin. It was concluded that the apigenin in Water Lily mango became bioaccessible, suggesting the absorption possibility of the compound in the upper part of intestine, which can lead to the health-related outcomes.